2016
DOI: 10.7150/ijms.14485
|View full text |Cite
|
Sign up to set email alerts
|

An Association Map on the Effect of Flavonoids on the Signaling Pathways in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the third most common type of cancer in the world, causing thousands of deaths annually. Although chemotherapy is known to be an effective treatment to combat colon cancer, it produces severe side effects. Natural products, on the other hand, appear to generate fewer side effects than do chemotherapeutic drugs. Flavonoids are polyphenolic compounds found in various fruits and vegetables known to possess antioxidant activities, and the literature shows that several of these flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 126 publications
2
66
0
1
Order By: Relevance
“…Based on their chemical structure, flavonoids can be divided in different subclasses 45,46 . Fisetin, a member of the flavonols family 43,47 , provides different beneficial effects through its anti-inflammatory 48 , antioxidant 49 , hypoglycemic 50 or anti-obesity 51 action. It is also known to have strong anti-cancer activity by inhibiting angiogenesis 52 , promoting cell cycle arrest in G 2 /M phase and by inducing apoptosis in cancer cells 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on their chemical structure, flavonoids can be divided in different subclasses 45,46 . Fisetin, a member of the flavonols family 43,47 , provides different beneficial effects through its anti-inflammatory 48 , antioxidant 49 , hypoglycemic 50 or anti-obesity 51 action. It is also known to have strong anti-cancer activity by inhibiting angiogenesis 52 , promoting cell cycle arrest in G 2 /M phase and by inducing apoptosis in cancer cells 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Flavone inhibits PI3K/AKT pathway to involve in the progression and apoptosis of cancer cells (18,30,31). Our previous results have presented that 100 µM flavone reduced viability slightly in breast cancer cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Many of them are part of human daily diet (15,16). Flavonoids inhibit PI3K/AKT pathway to induce apoptosis (17,18). Tangeretin inhibits growth of HL-60 cells and induces apoptosis without causing serious side-effect on immune cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms responsible for improvements in heart disease risk include improved endothelial function, decreased blood pressure, and improvements in lipid and insulin resistance. Flavonoids can be divided into the following subclasses flavonols, flavanones, flavones, flavan-3-ols, and flavanonols [22]. Koosha et al [22] reported relationship between flavonoid consumption and decreased cancer risk.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Flavonoids can be divided into the following subclasses flavonols, flavanones, flavones, flavan-3-ols, and flavanonols [22]. Koosha et al [22] reported relationship between flavonoid consumption and decreased cancer risk.…”
Section: Flavonoidsmentioning
confidence: 99%